Bloodstream infection among adults in Phnom Penh, Cambodia: key pathogens and resistance patterns. - Erika R Vlieghe (Public Library of Science (PLoS), 2013)
Background Bloodstream infections (BSI) cause important morbidity and mortality worldwide. In Cambodia, no surveillance data on BSI are available so far. Methods From all adults presenting with SIRS at Sihanouk Hospital Centre of HOPE (July 2007-December 2010), 20 ml blood was cultured. Isolates were identified using standard microbiological techniques; antibiotic susceptibilities were assessed using disk diffusion and MicroScan®, with additional E-test, D-test and double disk test where applicable, according to CLSI guidelines. Results A total of 5714 samples from 4833 adult patients yielded 501 clinically significant organisms (8.8%) of which 445 available for further analysis. The patients' median age was 45 years (range 15-99 y), 52.7% were women. HIV-infection and diabetes were present in 15.6% and 8.8% of patients respectively. The overall mortality was 22.5%. Key pathogens included Escherichia coli (n = 132; 29.7%), Salmonella spp. (n = 64; 14.4%), Burkholderia pseudomallei (n = 56; 12.6%) and Staphylococcus aureus (n = 53; 11.9%). Methicillin resistance was seen in 10/46 (21.7%) S. aureus; 4 of them were co-resistant to erythromycin, clindamycin, moxifloxacin and sulphamethoxazole-trimethoprim (SMX-TMP). We noted combined resistance to amoxicillin, SMX-TMP and ciprofloxacin in 81 E. coli isolates (62.3%); 62 isolates (47.7%) were confirmed as producers of extended spectrum beta-lactamase. Salmonella isolates displayed high rates of multidrug resistance (71.2%) with high rates of decreased ciprofloxacin susceptibility (90.0%) in Salmonella Typhi while carbapenem resistance was observed in 5.0% of 20 Acinetobacter sp. isolates. Conclusions BSI in Cambodian adults is mainly caused by difficult-to-treat pathogens. These data urge for microbiological capacity building, nationwide surveillance and solid interventions to contain antibiotic resistance.